2019
DOI: 10.1016/j.omtm.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Pre-clinical Safety and Efficacy of Lentiviral Vector-Mediated Ex Vivo Stem Cell Gene Therapy for the Treatment of Mucopolysaccharidosis IIIA

Abstract: Hematopoietic stem cell gene therapy is a promising therapeutic strategy for the treatment of neurological disorders, since transplanted gene-corrected cells can traffic to the brain, bypassing the blood-brain barrier, to deliver therapeutic protein to the CNS. We have developed this approach for the treatment of Mucopolysaccharidosis type IIIA (MPSIIIA), a devastating lysosomal storage disease that causes progressive cognitive decline, leading to death in early adulthood. In a previous pre-clinical proof-of-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Apart from the AAV-mediated treatment model, Orchard Therapeutics (London, UK) has started a Phase I/II ex vivo gene therapy using autologous CD34 + cells transfected with hSGSH-containing lentiviruses [134]. Pre-clinical data for this treatment modality demonstrated competency in meeting expected safety profiles and an effective transfection goal (2-5 copies/cell) [135]. This treatment model is the first of its kind in MPS clinical trials, and the preliminary results are highly anticipated.…”
Section: Gene Therapymentioning
confidence: 99%
“…Apart from the AAV-mediated treatment model, Orchard Therapeutics (London, UK) has started a Phase I/II ex vivo gene therapy using autologous CD34 + cells transfected with hSGSH-containing lentiviruses [134]. Pre-clinical data for this treatment modality demonstrated competency in meeting expected safety profiles and an effective transfection goal (2-5 copies/cell) [135]. This treatment model is the first of its kind in MPS clinical trials, and the preliminary results are highly anticipated.…”
Section: Gene Therapymentioning
confidence: 99%
“… 27 , 28 , 29 , 30 , 31 Similarly, promising results have been shown in pre-clinical studies in other lysosomal storage disorders such as globoid cell leukodystrophy 32 or mucopolysaccharidosis (MPS) diseases (MPS-I, MPS-II, or MPS-IIIA/B). 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 In these cases, the overexpression of the therapeutic gene in the HSPCs reduced the toxic accumulation of metabolites in affected tissues, ameliorating or even reverting, in the case of MPS-I, disease manifestations. Two previous studies looked at the feasibility of HSPC gene therapy in Pompe disease and showed a relevant decrease of glycogen accumulation in affected tissues upon treatment as well as the induction of immune tolerance versus hGAA in treated mice.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this process seems to be slow and not complete, making this option an invalid therapy for neurological disorders with a rapid progress of symptoms such as Sanfilippo syndrome, and currently, this approach is no longer considered for the treatment of Sanfilippo syndrome [ 97 ]. However, recent works using genetically modified hematopoietic stem cells carrying the normal copy of the SGSH or NAGLU genes showed an improvement in the neurological pathology in MPS IIIA or MPS IIIB mouse models [ 98 , 99 , 100 , 101 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%